An estimated of genetic parameters responses to selection in a population of irrigatec rice CNA 1. - Servellón, Ramón Eduardo (Agronomía Mesoamericana, 2016)
The experiments took place in the harvest year of 1993/1994 under rainfed lowland conditions, at the Experimental Field in Hacienda Palmital of the EMPRAPA-CNPAF, in Goianira, Brasil. We evaluated 97 families S 2:0 originally from the CNA 1 population, using as checks the cultivars BR IRGA 409 and JAVAE, and the population CNA 1/0/1. The experimental design utilized was a 10 x 10 lattice, with an utilization lot area of 0.60 m2. The objective was to evaluate the potentials of the CNA 1 population with the goal of improvement through the estima-tion of its genetic parameters and its direct and indirect responses to selection, as well as determining the classic Smith(1936) and Hazel (1943) indexes. The traits considered in the evaluation were the following: grain yield, leaf blast, date of flowering, plant height, spikelet number per panicle, percentage of filled grain and dry weight of 100 seeds. The results indicated the trait percentage of filled grains was the main priority for yield and the traits of production, leaf blast, plant height, spikelet number per panicle and percentage of filled grains showed a high genetic variability in the population, this was evident because of the hight estimates for coefficients of genetic variability. The highest responses for selection were obtained in the traits of production and plant height, both by direct selection or by utilization of the selection index. However, selection as per the classic Smith/ Hazel index showed more efficiency in relation to direct selection.